PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013 - 2015 - Agung Prasetyo; Wahyu Meiranto (Diponegoro Journal of Accounting, 2017)
Modern accounting concepts apply three basic principles of triple bottom lines, namely profit, people and planet (3P). Companies should still be oriented to seek economic benefits that allow it to continue to operate and grow. But the company must have concern for the welfare of human and the environment. Corporate Social Responsibility is a concept that connects these three principles. This study examines the influence of CSR on company performanceObject of this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) or year of 2013 to 2015. The dependent variable used is three proxies of profitability : ROA, ROE and EPS. Three linear regression analysis models were used for prove the hypoteses The results show that corporate social responsobility (CSR) has positive influence on ROA and ROE but not significant on EPS profitability. CSR can be viewed as one form of effort to form a positive image for company.